Beyond independent effects: The combined role of self-efficacy and organizational culture in work engagement - Firzan Ahmad Chirzin Paputungan; Unggul Haryanto Nur Utomo (Psychological Research and Intervention, 2025)
Work engagement is widely recognized as a critical driver of organizational effectiveness; however, its underlying psychological and organizational determinants remain a subject of ongoing debate. Self-efficacy and organizational culture are frequently identified as key antecedents of work engagement, yet empirical findings regarding their independent effects have been inconsistent. This study aims to examine both the joint and individual contributions of self-efficacy and organizational culture to work engagement. Employing a quantitative research design, data were collected from 50 employees of a hospitality organization in Yogyakarta using validated self-report scales. Multiple linear regression analysis revealed that self-efficacy and organizational culture jointly predicted work engagement (R = 0.561, p < 0.01). However, partial correlation analyses indicated that neither self-efficacy (r = 0.121, p > 0.05) nor organizational culture (r = 0.256, p > 0.05) demonstrated a statistically significant independent relationship with work engagement. These findings suggest that work engagement may emerge from the synergistic interplay between individual beliefs and organizational context rather than from isolated direct effects. Practically, the results imply that organizational interventions aimed at enhancing employee engagement should concurrently address both personal efficacy and cultural dimensions. Future research is encouraged to explore potential mediating or moderating mechanisms that may further elucidate the complex relationships among these variables.